Multivariate survival analysis for correlated node behavior in MANETS - Azni A.H.; Ahmad R.; Noh Z.A.M. (IEEE Computer Society, 2024)
This paper present correlated hazard function in multivariate network survival analysis in MANETS. Correlated hazard function is an extended hazard function in Cox model to capture correlated events. The function takes correlated degree as a covariate to measure the effect of correlated node behavior and describe the relationship between correlated degree and survival times. The covariates analysis shows that the effect of correlated degree is significant in measuring survival analysis in MANETS. 2014 IEEE.